Chloroplast DNA variation in the Turnera sidoides L. complex (Turneraceae): biogeographical implications - Speranza, Pablo R. (2007)
Aim: To analyse the current geographical structure of chloroplast DNA variation in the Turnera sidoides L. complex in order to establish historical biogeographical hypotheses for the mid‐latitude South American lowlands. During the Quaternary, the climate shifted from tropical humid to cold dry, and the vegetation cover has not been stable. The consequences of these processes on the current distribution of the vegetation of this area have received very little attention. Location: The mid‐latitude South American lowlands extend between c. 20 and 40°S and include Uruguay, northern, central and eastern Argentina, southern Brazil, and parts of southern Paraguay and Bolivia. They are surrounded by higher‐elevation systems. Methods: Turnera sidoides is a well‐studied polyploid complex of perennial rhizomatous herbs occurring throughout the area of interest. We analysed 321 individuals from 79 populations of the five recognized subspecies. We also included progenies from artificial crosses in order to analyse chloroplast inheritance. After screening sequences for four non‐coding chloroplast DNA regions, the trnL–trnF spacer was selected to characterize the collection. Results: Three haplotypes can be easily identified, with each differing from the others in two independent characters. A clear geographic structure is revealed when haplotypes are plotted for the complex as a whole regardless of subspecies and cytotype. Three distinct regions can be identified. Main conclusions: We propose three putative refugial areas for the Turnera sidoides complex, which are associated with the orographical systems of the region. Ravines and slopes in the Haedo Cuchilla system in northern Uruguay, the elevations of the western side of the area in Argentina, and the eastern Serranías system in south‐eastern Uruguay may each have served as refugia in which the A, B and C haplotypes became fixed during the drier climatic phases. Biogeographical patterns in the area covered by T. sidoides, particularly east of the Uruguay River, have not previously been analysed from a historical perspective. Location  The mid‐latitude South American lowlands extend between c. 20 and 40°S and include Uruguay, northern, central and eastern Argentina, southern Brazil, and parts of southern Paraguay and Bolivia. They are surrounded by higher‐elevation systems. Methods  Turnera sidoides is a well‐studied polyploid complex of perennial rhizomatous herbs occurring throughout the area of interest. We analysed 321 individuals from 79 populations of the five recognized subspecies. We also included progenies from artificial crosses in order to analyse chloroplast inheritance. After screening sequences for four non‐coding chloroplast DNA regions, the trnL–trnF spacer was selected to characterize the collection. Results  Three haplotypes can be easily identified, with each differing from the others in two independent characters. A clear geographic structure is revealed when haplotypes are plotted for the complex as a whole regardless of subspecies and cytotype. Three distinct regions can be identified. Main conclusions  We propose three putative refugial areas for the Turnera sidoides complex, which are associated with the orographical systems of the region. Ravines and slopes in the Haedo Cuchilla system in northern Uruguay, the elevations of the western side of the area in Argentina, and the eastern Serranías system in south‐eastern Uruguay may each have served as refugia in which the A, B and C haplotypes became fixed during the drier climatic phases. Biogeographical patterns in the area covered by T. sidoides, particularly east of the Uruguay River, have not previously been analysed from a historical perspective.